Spatial distribution of tumor-associated macrophages in an orthotopic prostate cancer mouse model - Korie A. Grayson; Korie A. Grayson; Joshua D. Greenlee; Lauren E. Himmel; Lauren A. Hapach; Lauren A. Hapach; Cynthia A. Reinhart-King; Michael R. King (Frontiers Media S.A., 2024)
Mounting evidence suggests that the immune landscape within prostate tumors influences progression, metastasis, treatment response, and patient outcomes. In this study, we investigated the spatial density of innate immune cell populations within NOD.SCID orthotopic prostate cancer xenografts following microinjection of human DU145 prostate cancer cells. Our laboratory has previously developed nanoscale liposomes that attach to leukocytes via conjugated E-selectin (ES) and kill cancer cells via TNF-related apoptosis inducing ligand (TRAIL). Immunohistochemistry (IHC) staining was performed on tumor samples to identify and quantify leukocyte infiltration for different periods of tumor growth and E-selectin/TRAIL (EST) liposome treatments. We examined the spatial-temporal dynamics of three different immune cell types infiltrating tumors using QuPath image analysis software. IHC staining revealed that F4/80+ tumor-associated macrophages (TAMs) were the most abundant immune cells in all groups, irrespective of time or treatment. The density of TAMs decreased over the course of tumor growth and decreased in response to EST liposome treatments. Intratumoral versus marginal analysis showed a greater presence of TAMs in the marginal regions at 3 weeks of tumor growth which became more evenly distributed over time and in tumors treated with EST liposomes. TUNEL staining indicated that EST liposomes significantly increased cell apoptosis in treated tumors. Additionally, confocal microscopy identified liposome-coated TAMs in both the core and periphery of tumors, highlighting the ability of liposomes to infiltrate tumors by "piggybacking" on macrophages. The results of this study indicate that TAMs represent the majority of innate immune cells within NOD.SCID orthotopic prostate tumors, and spatial density varies widely as a function of tumor size, duration of tumor growth, and treatment of EST liposomes.